A preliminary study on the efficacy of the V4 Newcastle disease vaccine when administered through drinking water and as aerosols - Ibrahim, A. Latif; Ungku Mohsin, Ungku Chulan; Babjee, A. Mustaffa (Persatuan Doktor Veterinar Malaysia, 1979)
Vaccinatioll of chickens by the intranasal, aerosol or the drinking water method at 14 and 35 days old stimulated satisfactory haemagglutination inhibition (HI) antibody response which persisted for 9 weeks. The antibody response to aerosol or intranasal vacr.ination was slightly higher than the drinking water vaccination at the time of challenge. Chickens oaccinated by intranasal or aerosol or drinking zoater method were resistant when challenged with the virulent Newcastle disease virus (NDV).